HV/HR-CMOS sensors for the ATLAS upgrade: concepts and test chip results - Liu, J.; Backhaus, M.; Barbero, M.; Bates, R.; Blue, A.; Bompard, F.; Breugnon, P.; Buttar, C.; Capeans, M.; Clemens, J. C.; Feigl, S.; Ferrere, D.; et al. (Journal of Instrumentation, 2015)
In order to extend its discovery potential, the Large Hadron Collider (LHC) will have a major upgrade (Phase II Upgrade) scheduled for 2022. The LHC after the upgrade, called High-Luminosity LHC (HL-LHC), will operate at a nominal leveled instantaneous luminosity of 5× 1034 cm−2 s−1, more than twice the expected Phase I . The new Inner Tracker needs to cope with this extremely high luminosity. Therefore it requires higher granularity, reduced material budget and increased radiation hardness of all components. A new pixel detector based on High Voltage CMOS (HVCMOS) technology targeting the upgraded ATLAS pixel detector is under study. The main advantages of the HVCMOS technology are its potential for low material budget, use of possible cheaper interconnection technologies, reduced pixel size and lower cost with respect to traditional hybrid pixel detector. Several first prototypes were produced and characterized within ATLAS upgrade R&D effort, to explore the performance and radiation hardness of this technology. In this paper, an overview of the HVCMOS sensor concepts is given. Laboratory tests and irradiation tests of two technologies, HVCMOS AMS and HVCMOS GF, are also given.